Pengembangan Media Pembelajaran Matematika Model e-learning Berbasis Web pada Materi Trigonometri di Kelas XI SMK - Husniati, Kholis; Hariyani, Sri; Fayeldi, Trija (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2022)
Technology is growing rapidly, one of which is in the aspect of education. E- learning media can be a means to apply technological developments by utilizing facilities in schools such as the internet. ADDIE development model is used in this development research. This study aims to develop an e-learning model of learning media and to determine the validity and practicality of the media as teaching materials for teachers and learning media for students. The research instrument used was a validation sheet and a google form response questionnaire. The validity of e-learning media is based on the results of the media expert's validation score of 3.67 and material expert 3.53, both of which are valid criteria. The practicality of the media according to the results of expert practitioner assessments and the responses of 10 students in a limited trial was 3.60. As for the practicality in the broad trial as many as 29 students were obtained at 3.42 in practical criteria. Thus it can be concluded that learning mathematics on trigonometric material is valid and practical using web-based e-learning learning media.